Further Evidence of von Willebrand Factor Involvement in Thrombotic Thrombocytopenia Purpura - Chediak, J; Eldridge, J; Bergmann, F; Sobel, D; Baron, J; Maxey, B; Telfer, M C (Thrombosis and Haemostasis, 1988)
Fourteen patients diagnosed as having thrombotic thrombocytopenia purpura (TTP) were studied. Those who survived have been followed during a 1 to 7 year period. The clinical diagnosis was based on changing neurological findings, thrombocytopenia and evidence of microangiopathic hemolytic anemia. Laboratory tests included the determination of von Willebrand factor antigen (VWF:Ag), ristocetin cofactor (RiCof) and the electrophoretic mobility of von Willebrand factor (CIE VWF:Ag). The ratio of RiCof to VWF:Ag was then calculated. Control individuals included healthy subjects and patients with thrombocytopenia of several etiologies. Statistical differences between the values of RiCof, the ratio of RiCof : VWF: Ag and the CIE of VWF: Ag were found for samples comparing active disease and remission phase. The recovery from thrombocytopenia paralleled the correction of abnormal parameters. Similarly, significant differences were found when above parameters were compared between thrombocytopenia of TTP with other thrombocytopenic states. We suggest that these abnormal tests could be useful in distinguishing TTP from other disorders, and may have prognostic significance in patients already diagnosed as having TTP.
Keywords: Thrombotic thrombocytopenia purpura (TTP); von Willebrand factor antigen (VWF : Ag); Ristocetin cofactor (RiCof)